Scale-up of the DMPA-SC in Nigeria: Why policy matters - Oluwaseun Akinyemi; Nicole Danfakha; Adewole Adefalu; Ebony Easley; Kayode Afolabi; Olajimi Latunji (BMC Women's Health, 2022)
Abstract Background Injectable contraceptives have contributed substantially to Nigeria's rise in modern family planning methods usage. They are one of the most commonly used and preferred means of contraception among women in the country. Enabling policies are required to assure contraceptive access, security, and use. This study aimed to investigate the policy environment and how it supports or limits Nigeria's introduction and scale-up of subcutaneous depot-medroxyprogesterone acetate (DMPA-SC). Methods The design of this mixed-methods study was cross-sectional. Desk reviews of policy papers, key informant interviews, and in-depth interviews were used to obtain information from respondents about the introduction of DMPA-SC in Nigeria and how existing policies influenced its scale-up. Data on DMPA-SC and other injectables were gathered from Nigeria's national electronic logistics management information system. Results The findings suggest that policies such as task-shifting and task-sharing, cost-free policies, reproductive health policies, and others created an enabling environment for the scale-up of DMPA-SC adoption in Nigeria. The inclusion of DMPA-SC on the essential medicines list and the approved patent medicines list facilitated the scale-up process by ensuring private sector participation, removing economic barriers to access, fostering greater collaboration among health worker cadres, improving intersectoral partnerships, and improving logistics and client access. Despite significant anomalies in some implementing policies, injectable contraceptive consumption data demonstrate a progressive increase in DMPA-SC use during the study period. The results also indicate that policy initiatives have a favorable impact on the use of DMPA-SC throughout the country. Conclusion The existence of policies, the active participation of stakeholders, and the political will of the Nigerian health system's leadership have all aided in the scaling-up of the DMPA-SC. Understanding how to build an enabling policy climate is critical for providing women with family planning options. These lessons from Nigeria emphasize the importance of these levers, which should be considered by teams intending to introduce innovative health products, particularly in developing countries.